Analisis Perbandingan Infrastruktur Transportasi Di Negara Indonesia Dan Jepang - Ritonga, Fajar Fernando; Dompak, Timbul (Prosiding, 2024)
Transportation infrastructure development is one of the important aspects needed to increase a country's economic growth. In Indonesia, transportation infrastructure development in the next 15 years is estimated to require an investment of IDR 1,785 trillion. This figure includes Rp 339 trillion for roads, Rp 117 trillion for ports, Rp 32 trillion for airports, and Rp 326 trillion for railways. The Public Private Partnership (PPP) approach is used in infrastructure development programs as one of the financing alternatives for transportation infrastructure projects in Indonesia. This article aims to discuss the history of PPP policy development in Indonesia. This article aims to discuss the history of PPP policy development in Indonesia in an effort to create Esteem for Cash in infrastructure development projects. In addition, it also discusses various studies on the key factors of successful implementation of PPP schemes in other countries and the Indonesian government's strategic steps to produce various policies that support the implementation of PPP schemes from 2005-2020